Calendar for gardening in May-June - Janakiram, T.; Jain, Ritu; Namita, Namita; Lakshmipathy, M. (Indian Horticulture, 2019)
May and June are hottest months in the plains where temperature hovers around 40Â°C. Major emphasis should be given to protect the plants from scorching heat as well as conservation of soil moisture. During these months, most of the planning and preparation can be done for coming monsoon season. The garden enthusiasts can enjoy the array of colours in flowering trees like Jacaranda, Bignonia, Albezzia lebbeck, Cassia fistula, Cassia nodosa, Delonixregia, Magnolia; shrubs like Allamanda, Adenium, Murraya, Russelia, Cestrum etc. Along with these trees and shrubs, some climbers like Aristolachia, Solanum jasminoides, Wisteria, Quisqualis indica, Clerodendron, Trachelospermum also bear showy and colourful flowers.